Myocardial Epithelial Inclusions in a Bovine Fetus - Eroksuz, Yesari; Karabulut, Burak; Incili, Canan Akdeniz; Kara, Emel; Cankaya, Eren; Eroksuz, Hatice (Hellenic Veterinary Medical Soc, 2024)
Myocardial epithelial inclusions (MEIs) were identified in a 6-month-old aborted Simmental breed fetus through gross, histopathological, and immunohistochemical assessments. Grossly; a circular, unencapsulated white lesion, in 2.5 mm diameter was detected on the free wall of the left ventricular myocardium. Histopathological examination showed a densely cellular focus with tubular, ductular, or acinar structures surrounded by abundant collagen. Immunohistochemically, the acinar and tubular cells showed strong cytoplasmic immunoreactivity to cytokeratin and vimentin. As a result, this report represents first reported case MEI in a bovine fetus and it emphasizes the necessity of add the differentials of MEIs during postmortem examinations, including the fetal period in cattle.
Keywords: Bovine; Epithelial Inclusions; Fetus; Immunhohisochemistry Myocardium; Pathology.